2019
DOI: 10.1016/j.nmni.2019.100597
|View full text |Cite
|
Sign up to set email alerts
|

Molecular serotyping and genotyping of penicillin non-susceptible pneumococci: the introduction of new sequence types, Tehran, Iran

Abstract: The emergence of penicillin non-susceptible Streptococcus pneumoniae (PNSP) isolates can pose significant challenges to today's health-care system. Resistant clonal isolates are disseminated in different regions and countries, and this study was focused on the description of the epidemiological spread of these strains. Clinical samples were collected from individuals admitted to hospitals affiliated to the Tehran University of Medical Sciences, Iran. To investigate the molecular characteristics of PNSP isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…But, vaccination against the most common serotypes of S. pneumoniae using PCVs is not still included to the routine immunization program in the Iran and only recommended for high-risk groups [28]. The present study, in addition to others from Iran, shows that the PCV13 could cover the majority of the invasive pneumococcal isolates [19,20,28,29].…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…But, vaccination against the most common serotypes of S. pneumoniae using PCVs is not still included to the routine immunization program in the Iran and only recommended for high-risk groups [28]. The present study, in addition to others from Iran, shows that the PCV13 could cover the majority of the invasive pneumococcal isolates [19,20,28,29].…”
Section: Resultsmentioning
confidence: 65%
“…Habibi Ghahfarokhi et al observed that the common serotypes isolated from clinical samples were 23F, 14, 3, 19F and 19A [28]. In another study by Azarsa et al in Iran, the common serotypes isolated from clinical samples were 23F, 19F, 14, 3 and 9 V [29]. In Japan, Sakata et al evaluated 142 cases of IPD and observed that the most frequently serotypes were 6B, followed by 23F and 19F [30].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we revealed that the rates of PNSP were 100%, 44%, 25%, and 25% for serotypes 6B, 6C/6D, 14, and 19B/19C, respectively. Notably, in China, PNSP was commonly detected among serotypes 23F (81.4%), 19F (70.7%), 19A (97.6%), 14 (77.8%), and 6A (66.7%) isolated from invasive infections [ 41 ]. The persistence of PNSP in healthy carriers following the introduction of PCV10 is likely associated with high usage of antibiotics, which may exert significant pressure driving S. pneumoniae strains to acquire antibiotic resistance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%